Clinicopathological Features of Gallbladder Carcinoma Managed in a Tertiary Level Hospital of Nepal - Dahal, Romi; Ghimire, Bikal; Kansakar, Prasan BS; Lakhey, Paleshwan Joshi; Bhandari, Ramesh S (Journal of Institute of Medicine Nepal, 2021)
Introduction: Gallbladder carcinoma is a relatively rare disease in some parts of the world but is common in countries like Chile, Japan, India, and Nepal. Nepal stands as one of the five countries with the highest mortality. However, there are only a few studies published on this matter from Nepal. This study aims to study the demographic and clinicopathological features of gallbladder carcinoma managed in a tertiary level teaching hospital in Nepal.Methods: A retrospective analysis of all the patients with the diagnosis of gall bladder carcinoma in Tribhuvan University Teaching Hospital from 2018 to 2020 was done. Patient demographics, clinical characteristics, and laboratory parameters including tumor markers were analyzed.Results: Of the 59 patients, there were 33 (56%) females. The median age at diagnosis was 56 years. Among all, the most common presenting symptom was abdominal pain. Curative resection was done in 18 (30%) of the cases. Metastasis was present in 30% of the cases of which the liver was the most frequently involved organ. The mean carcinoembryonic antigen (CEA) level in unresectable cases was 18.65±22.53 nanograms per milliliter (ng/mL) which was higher than in resectable cases being 6.78±12.75 ng/mL. Similarly, the mean carbohydrate antigen 19-9 (CA 19-9) level in unresectable cases was 604.55±671.28 units/milliliter (U/ml), which was higher than the value in the resectable cases 89.44±273.67 U/ml.Conclusion: In this study, gall bladder carcinoma was more common in females below 60 years with vague abdominal pain as the most frequent presenting symptom. One-third of the evaluated cases were resectable. Unresectable cases were associated with high CEA and CA 19-9 levels.